Shopping malls, platforms and consumer search - Parakhonyak, A; Titova, M (Elsevier, 2018)
We consider a model of a market for differentiated goods in which firms are located in marketplaces e.g., shopping malls or platforms. There are search frictions between marketplaces, but not within. Marketplaces differ in size. We show that an equilibrium in which consumers start their search at the largest marketplace and continue in the descending order of size, always exists. Despite charging lower prices, firms in larger marketplaces earn higher profits. Under free entry, all firms cluster in one marketplace provided that search frictions are large enough. If a marketplace determines the price of entry, then the equilibrium marketplace size is a single-peaked function of search costs and is decreasing for most of the search cost range.